1991
DOI: 10.1111/j.1600-0447.1991.tb03157.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medical school stress on the mental health of medical students in early and late clinical curriculum

Abstract: Earlier research has shown that medical students in the United Kingdom and the United States report a higher level of nervous symptoms than the general population. To better understand how medical students in Norway compare with these findings, 299 male and female students in the clinical curriculum at the University of Oslo were asked to complete a questionnaire about themselves and their mental health. Medical students in Norway do not differ from the general population in mental health. However, the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
109
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 16 publications
3
109
0
16
Order By: Relevance
“…[12][13][14][15][16] Numerous studies have documented QoL issues amongst the medical student population. 1,[3][4][5][6] For example, research has indicated the adverse impact of medical education on student well-being, and these issues have been linked to the intense nature of the academic, clinical, and professional demands made during training and problems related to finance and expectations from staff and parents. 4,5,[17][18][19] The notion of QoL has been defined by the World Health Organization (WHO) as "individuals" perceptions of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] Numerous studies have documented QoL issues amongst the medical student population. 1,[3][4][5][6] For example, research has indicated the adverse impact of medical education on student well-being, and these issues have been linked to the intense nature of the academic, clinical, and professional demands made during training and problems related to finance and expectations from staff and parents. 4,5,[17][18][19] The notion of QoL has been defined by the World Health Organization (WHO) as "individuals" perceptions of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns".…”
Section: Introductionmentioning
confidence: 99%
“…1 There is considerable interest in medical students and the driving forces that underpin their learning process. 2 The well-being of medical students is well researched, and some links have been made between students" quality of life and their motivation to learn, and scholastic achievement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of distress such as the symptoms of depression is found to be high (3,4), leading to an increased tendency to commit suicide (5,6). The performance of students in the classroom as well as in clinical practice is greatly affected in the presence of emotional distress, leading to stressrelated disorders (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the prevalence of depression among people younger than 20 years of age has increased worldwide (2) . It is estimated that the prevalence of depression among the young population might reach 8.3% (3) and that the frequency of depression is higher among students than in the population in general (4)(5) . Therefore, university students have been a target of studies addressing mental disorders.…”
Section: Introductionmentioning
confidence: 99%